Informed consent: knowledge, attitude and practice of the researchers in a postgraduate institute of Bangladesh - Shakoor, MA; Jaigirdar, QH; Ullah, MA; Yunus, AB; Rashid, HA (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):215-20. The abstract of this article is available on the PubMed website